The Girl Who Wasn't There (Mac Detective Mysteries, ,, 2015)
The trail Mac found himself trying to follow was very cold. Another private detective - his friend Barry Henley - had been killed a year earlier in a fall from a tenth-story window, and the cops had written it off as accidental. But when Hensley's widow told Mac that several people had tried to get into her apartment under various pretexts; when Mac found she was being followed; and when the mug shot she picked out of the police department files proved to be that of a very tough egg, Whiskey Davis - suddenly Henley's death began to look like murder. Mac knew for sure when the next death couldn't have been accidental. A bomb that blows up car and driver when the ignition is turned is never anything but murder... "Mac is one of our best private eyes." - San Francisco Chronicle "Thomas B. Dewey is one of detective fiction's severely underrated writers!" - Bill Pronzini "More than one rub-out for private eye Mac to run through when a man with a well-minked wife is shot down by a police sergeant from Steel City, outside of Chicago. Exit also for an attorney, a safecracker and assorted others who are linked to the importance of teenage Marianne, the rehabilitation project of moneyman Lloyd, and a series of black-mailing pictures. Scrappy all the way." - Kirkus Reviews "Mac has been called one of the most believable and humane PI's in crime fiction. He is reluctant to use either his gun or his fists, but will do so when the situation demands it, or in self-defense; he doesn't merely solve his clients' cases, but provides moral support and sympathy as well; and perhaps most notable of all, Mac feels, and is not afraid to show itópain, loss, sorrow, loneliness." -thrillingdetective.com

Deadline (Mac Detective Mysteries, ,, 2018)
Deadline sends Mac to a small town on a tight deadline to save a boy from execution for a brutal murder. Mac makes a beautiful job of it despite the townsfolk's violent hostility. #13 in the Mac detective series!

Fifteen Reasons to Kill (Detective Inspector Jack MacIntosh Mysteries, ,, 2023)
An absolutely gripping crime thriller with a massive twist. Eighty-one-year-old Eddie Wakefield is found brutally murdered at the nursing home where he lives. Crudely carved into his flesh-while he was still alive-is the number fifteen. Detective Jack MacIntosh and his team are determined to track down the ruthless killer of this frail elderly man. But the investigation is leading nowhere. Then the second body is discovered. The victim was stabbed to death in their own home. Again, the number fifteen is etched into the dead man's flesh. A single clue leads to St Bartholomew's School for Boys, a grim and forbidding institution on England's south coast-and a series of shocking secrets stretching back more than forty years. What is the significance of the number fifteen . . . and is Jack prepared for the horrifying truth?

Seven Days to Die (Detective Inspector Jack MacIntosh Mysteries, ,, 2023)
A twisted killer. A deadly game of cat-and-mouse. Detective Jack MacIntosh has seven days to find the truth. A young woman is discovered strangled in Hyde Park. Wearing only one shoe. Close to the body, Detective Jack MacIntosh finds a black stiletto, diamante buckle glinting in the early morning sun. But it doesn't belong to the victim. Two days later, another young woman is found strangled to death in nearby Green Park. Wearing just one shoe-the matching stiletto. Hidden in the long grass beside the body, the police uncover a low-heeled court shoe. Detective Jack and his team are in a race against time to find the owner of the court shoe before it's too late. At the same time, Jack is fighting demons of his own. Demons which rise up from the past and threaten to cloud his judgement just when he needs it most. Detective Jack is hunting a brutal killer. A killer who delights in playing twisted games. Who will win this deadly battle of wits?

Sixteen Carved Pieces (Detective Inspector Jack MacIntosh Mysteries, ,, 2023)
An absolutely gripping crime thriller with a massive twist Billie-Rose's bloodstained body is found in the kitchen of her ground-floor flat. She's been strangled to death, there's a deep laceration to her upper thigh, and a wooden chess-piece grasped tightly in her hand. Daubed on the wall in Billie-Rose's own blood is a strange symbol: a bishop's mitre. All Detective Jack MacIntosh can think is: He's back. Four years earlier, four young women were also strangled to death in their own homes, the same deep wound to the thigh, the same weird symbol scrawled on the wall. The work of the killer they call the Bishop. Is he back to kill again? Jack and his team are in a race against time to pull the pieces together and uncover the truth before more young women die. Perfect for fans of Helen H. Durrant, Biba Pearce, Lynda La Plante, Angela Marsons, and Rachel McLean.

Twenty Years Buried (Detective Inspector Jack MacIntosh Mysteries, ,, 2023)
MEET DETECTIVE JACK MACINTOSH IN THIS BRILLIANT NEW CRIME SERIES. An absolutely gripping crime thriller with a massive twist. The call comes in the early hours. Human remains have been discovered in a suitcase, dumped on the muddy banks of the River Thames. Detective Jack MacIntosh races to the scene. The suitcase contains a human torso, two arms and two legs. It's the body of a young girl. But where is her head? Then a skull is found embedded in the silt of the riverbed. But it doesn't belong to the body in the case. As the river offers up more of its gruesome secrets, Jack uncovers a tangled web of shocking secrets stretching back twenty years.